(untitled) (Contemporary Journal of Social Science Review, 2026)
Vocabulary selection constitutes a foundational concern in English language teaching, as the principle of maximum output with minimum input guides pedagogical decision-making regarding which lexical items to prioritize for instruction (Nation, 2006). This study presents a comparative analysis of two influential high-frequency word lists: the New General Service List (NGSL; Browne et al., 2013) and the British National Corpus-Corpus of Contemporary American English 25 (BNC-COCA 25; Nation, 2012). Through vocabulary profiling using Lextutor (Cobb, 2022), the study examines the degree of overlap, divergence, and coverage potential of these lists to inform vocabulary teaching and assessment practices. The analysis reveals substantial convergence between the two lists, with only five NGSL words (bedroom, forever, online, shareholder, weekend) absent from the BNC-COCA first three levels due to their status as compound words. The BNC-COCA first three levels contain 612 additional word families beyond the NGSL, suggesting broader coverage potential. The findings indicate that both lists demonstrate high utility for general English instruction, though the BNC-COCA lists offer enhanced coverage for pedagogical applications. The study discusses implications for curriculum design, materials development, and learner assessment, arguing that corpus-derived word lists should serve as benchmarks for systematic vocabulary instruction rather than prescriptive constraints on lexical selection.